From Text to Context : The Turn to History in Modern Judaism - Schorsch, Ismar (Book collections on Project MUSE., 1994)
... Shows how the Wissenschaft des Judentums movement, which advocated a more scientific study of Judaism, "was to make historical thinking the dominant universe of discourse in Jewish life and historians its major intellectual thinkers.